Food purchase behaviour in a Finnish population: patterns, carbon footprints and expenditures. Issue 11 (18th November 2022) - Meinilä, Jelena; Hartikainen, Hanna; Tuomisto, Hanna L; Uusitalo, Liisa; Vepsäläinen, Henna; Saarinen, Merja; Kinnunen, Satu; Lehto, Elviira; Saarijärvi, Hannu; Katajajuuri, Juha-Matti; Erkkola, Maijaliisa; Nevalainen, Jaakko; et al.
Abstract: Objective: To identify food purchase patterns and to assess their carbon footprint and expenditure. Design: Cross-sectional. Setting: Purchase patterns were identified by factor analysis from the annual purchases of 3435 product groups. The associations between purchase patterns and the total purchases' carbon footprints (based on life-cycle assessment) and expenditure were analysed using linear regression and adjusted for nutritional energy content of the purchases. Participants: Loyalty card holders ( n 22 860) of the largest food retailer in Finland. Results: Eight patterns explained 55 % of the variation in food purchases. The Animal-based pattern made the greatest contribution to the annual carbon footprint, followed by the Easy-cooking, and Ready-to-eat patterns. High-energy, Traditional and Plant-based patterns made the smallest contribution to the carbon footprint of the purchases. Animal-based, Ready-to-eat, Plant-based and High-energy patterns made the greatest contribution, whereas the Traditional and Easy-cooking patterns made the smallest contribution to food expenditure. Carbon footprint per euros spent increased with stronger adherence to the Traditional, Animal-based and Easy-cooking patterns. Conclusions: The Animal-based, Ready-to-eat and High-energy patterns were associated with relatively high expenditure on food, suggesting no economic barrier to a potential shift towards a plant-based diet for consumers adherent to those patterns. Strong adherence to the Traditional pattern resulted in a low energy-adjusted carbon footprint but high carbon footprint per euro. This suggests a preference for cheap nutritional energy rather than environment-conscious purchase behaviour. Whether a shift towards a plant-based pattern would be affordable for those with more traditional and cheaper purchase patterns requires more research.